Unveiling alcohol bias and impaired inhibitory control in young binge drinkers: insights from the alcohol hayling task - Carina Carbia; Natália Almeida-Antunes; Margarida Vasconcelos; Eduardo López-Caneda (Scientific Reports)
Abstract Craving and alcohol-related bias play a central role in addiction development. Previous research suggests that individuals with alcohol misuse exhibit heightened alcohol bias and deficits in inhibitory control, contributing to increased craving and sustained consumption. However, this relationship remains poorly understood in young binge drinkers, particularly regarding a specific form of bias known as semantic alcohol bias (heightened automatic accessibility of alcohol-related concepts), which may influence craving and drinking behavior. The present study is aimed at addressing this gap. A total of 81 college students (41 Binge Drinkers and 40 Non/Low Drinkers) completed craving questionnaires and the Alcohol Hayling task, a sentence-completion paradigm designed to measure semantic alcohol bias and inhibitory control. Results revealed that young binge drinkers generated more alcohol-related words in drinking-context sentences, committed more errors (i.e., producing alcohol-related words when they should have generated unrelated words), and displayed slower response times when inhibiting alcohol-related responses. A positive correlation was observed between craving and the frequency of alcohol-related words. These findings suggest that young binge drinkers exhibit a semantic accessibility bias towards alcohol-related concepts and difficulties inhibiting alcohol-related content. This study highlights the role of alcohol-related semantic networks in craving states, providing new insights into how alcohol biases may contribute to binge drinking behaviors among youth.